YOGA SEBAGAI TERAPI NON-FARMAKOLOGI UNTUK MENANGANI NYERI DISMENOREA PADA REMAJA PUTRI - Soraya, Desi; Nurhanifah, Tia; Aldila, Silvy; Saadah , Anifatus (LPPM Universitas Awal Bros, 2025)
Dysmenorrhea pain is one of the common health problems experienced by adolescent girls and can interfere with daily activities. Pharmacologically managing dysmenorrhea pain often raises concerns about long-term side effects, so effective non-pharmacological alternatives are needed. This community service program aims to introduce yoga as a non-pharmacological therapy that can help reduce dysmenorrhea pain. The participants consisted of 20 students from class X and XI. This activity involves adolescent girls who experience dysmenorrhea pain with the implementation of counseling and yoga practices focused on pelvic muscle stretching, relaxation, and breathing regulation as well as the provision of leaflets, PowerPoint presentations, and yoga videos. The provision of counseling and simulation of dysmenorrhea yoga movements which was previously 90% unknown became a complete increase in understanding (from 10% to 100%) of the students who were also able to do yoga movements independently step by step accordingly. Most of the participants were satisfied as much as 80% with this activity, 5 students were menstruating and were experiencing dysmenorrhea mentioning that yoga was easy to follow and had a positive effect on dysmenorrhea pain.